Pengaruh Manajemen Laba Akrual, Manajemen Laba Riil dan Intensitas Persediaan terhadap Agresivitas Pajak - Riris Choirunnisa (Reviu Akuntansi, Manajemen, dan Bisnis, 2022)
Purpose : This study aims to determine the effect of accrual earnings management, real earnings management, and inventory intensity on tax aggressiveness in manufacturing companies in the consumer goods industry sector in Indonesia. Research methodology : The sampling method used is a purposive sampling technique with a sample of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) in 2018-2019. The analytical tools used in This research is multiple linear regression analysis. Data were analyzed using SPSS version 22. Results : The results of this study indicate that accrual earnings management has no effect on aggressiveness, real earnings management has a negative effect on tax aggressiveness, inventory intensity has no effect on tax aggressiveness, and accrual earnings management, real earnings management and inventory intensity are tested together have a positive effect on tax aggressiveness. Limitations : This study only uses three independent variables while there are many other variables that can be used affect tax aggressiveness. Contribution : This research is expected to provide information for companies to be considered in making tax savings so that they do not tend to enter into tax aggressiveness action.